Study on the metabolic effects of hexavalent chromium [Cr (VI)] on rat astrocytes using un-targeted metabolomics - Tang, Hongge; Li, Kunyang; Lin, Lin; Wang, Wenying; Jian, Wenjie (Frontiers in Molecular Biosciences, 2024)
Hexavalent chromium (Cr (VI)) has been confirmed as a human carcinogen and environmental pollutant, capable of influencing multiple systems in the human body. However, the mechanism by which Cr (VI) affects the human nervous system remains unclear. In this study, following the confirmation of the toxic effects of Cr (VI) on rat astrocytes, we investigated the metabolites of rat astrocytes and the associated metabolic pathways under different doses of Cr (VI) exposure. The research findings are as follows: the viability of astrocytes significantly decreases with increasing doses of Cr (VI), as observed through CCK8 experiments. This decrease is accompanied by elevated levels of intracellular reactive oxygen species (ROS) and 8hydroxydeoxyguanosine (8-OHdG), along with increased caspase-3 activity. Key metabolites affected by Cr (VI), as determined by un-targeted metabolomics, include sphingosine and methionine. Furthermore, there are variations in the metabolic products influenced by different doses of Cr (VI). The enrichment analysis of KEGG pathways revealed that sphingolipid metabolism and the methionine-cysteine cycle play crucial roles in the impact of Cr (VI) on rat astrocytes. In summary, our study provides preliminary research data for future treatment and prevention efforts.